2008
DOI: 10.1007/s10517-009-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autologous Bone Marrow Cells on Apoptosis and Regeneration of Non-Healing Autoimmune Gastric Ulcers

Abstract: The effects of cultured autologous bone marrow multipotent mesenchymal stromal cells on apoptosis and healing processes were studied on the model of non-healing gastric ulcers in rats. Bone marrow multipotent mesenchymal stromal cells inhibited apoptosis in epitheliocytes of the gastric mucosa and stimulated ulcer healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, Askarov et al reported that acceleration of ulcer regeneration by BM-MSCs transplantation was attributed to an increase in the levels of proinflammatory cytokines (IL-10, IL-4, transforming growth factorbeta (TGF-β)) with simultaneous reduction in the expression of apoptosis marker (caspase-9). So, BM-MSCs could regulate the apoptosis activity in the gastric mucosa [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Askarov et al reported that acceleration of ulcer regeneration by BM-MSCs transplantation was attributed to an increase in the levels of proinflammatory cytokines (IL-10, IL-4, transforming growth factorbeta (TGF-β)) with simultaneous reduction in the expression of apoptosis marker (caspase-9). So, BM-MSCs could regulate the apoptosis activity in the gastric mucosa [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-mesenchymal stem cells (BMMSCs) were reported by multiple studies to have a valuable role in the gut damage healing and contribute to the gastrointestinal tissue's development (Liu et al, 2015). Askarov et al (2008) found that multipotent mesenchymal stromal cells derived from autologous bone marrow may promote gastric mucosa microcirculation, stimulate angiogenesis, and enhance gastric ulcer healing in rats This study aimed to assess 5-FU effect on gastric mucosa and compare between the beneficial regenerative effects of BMMSCs and Astaxanthin on 5-FU-induced gastric toxic lesions.…”
Section: Introduction mentioning
confidence: 99%